(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Even children know that one drop of nicotine can kill a horse. However, this argument does not make a special impression on smokers: they fool themselves with the statement that it is impossible to smoke so many cigarettes at the same time. However, the harm of tobacco smoke is not related to nicotine itself, it only causes addiction, the destructive effects of smoking are also expressed by other factors.